Asthma and allergic rhinitis in childhood: what's new. Issue 8 (December 2016) - Mastrorilli, Carla; Posa, Daniela; Cipriani, Francesca; Caffarelli, Carlo
Abstract: Novel approaches are currently offered for the diagnostic workup and therapeutic management of allergic rhinitis and asthma. New predictive biomarkers of allergy and asthma are available. Primary and secondary prevention, earlier intervention, and modification of the natural history of allergic rhinitis and asthma are being intensively investigated. This review highlights advances in the understanding of the etiology, diagnosis, and management of atopic airway diseases in childhood, as well as prenatal and early‐life risk factors and strategies for prevention.